Access to information on the posting of third-country nationals - Vah Jevšnik, Mojca (Dve domovini, 2025)
In recent years, it has been observed that workers who are being posted to provide services in the EU Member States are not only EU nationals but also third-country nationals (TCNs). The overlap of migration, employment regimes, and cross-border mobility has been particularly notable in specific labor-intensive sectors in Slovenia, such as construction, where the overall share of posted TCNs has reached over 43%. The challenges and needs of the posting companies in accessing and using relevant information regarding the posting of TCNs that may be subject to additional countryspecific conditions and regulations are manifold. The problem is exacerbated further when company owners are TCNs themselves. The article gives an overview of the challenges of the employers and TCN-posted workers in terms of their access and use of information on the posting of workers, focusing mainly on the impediments due to language barriers.
Keywords: dostop do informacij; državljani tretjih držav; labour market; migracije; migration; napotitve delavcev; posting of workers; Slovenia; Slovenija; third-country nationals; trg dela